MINAT DAN MOTIVASI BELAJAR SEBAGAI PREDIKTOR CAPAIAN AKADEMIK MAHASISWA (STUDI KASUS PADA MAHASISWA UNIVERSITAS DELI SUMATERA) - Icha Dwi Paluvi; Mustika Dewi; Syukron Firdaus Siregar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Students’ perceptions of their academic achievement are influenced by various internal factors, including interest in learning and motivation to learn. The purpose of this study is to examine the influence of interest in learning and motivation to learn on the perceptions of academic achievement among students at Deli Sumatera University. This study adopted a quantitative method with a causal-associative research design. The sample was selected using simple random sampling. Data collection was conducted using a questionnaire, which was then analyzed using multiple linear regression. The study’s findings indicate that both interest in learning and motivation to learn have a positive and significant effect—both partially and simultaneously—on students’ perceptions of their academic achievement. These results suggest that efforts to enhance interest in and motivation for learning are significant in improving students’ academic achievementStudents’ perceptions of their academic achievement are influenced by various internal factors, including interest in learning and motivation to learn. The purpose of this study is to examine the influence of interest in learning and motivation to learn on the perceptions of academic achievement among students at Deli Sumatera University. This study adopted a quantitative method with a causal-associative research design. The sample was selected using simple random sampling. Data collection was conducted using a questionnaire, which was then analyzed using multiple linear regression. The study’s findings indicate that both interest in learning and motivation to learn have a positive and significant effect—both partially and simultaneously—on students’ perceptions of their academic achievement. These results suggest that efforts to enhance interest in and motivation for learning are significant in improving students’ academic achievement